Enhanced radiofrequency ablation for recurrent hepatocellular carcinoma post-transarterial chemoembolization: a prospective study utilizing twin internally cooled-perfusion electrodes - Sungjun Hwang; Jae Hyun Kim; Sae-Jin Park; Su Jong Yu; Yoon Jun Kim; Jung-Hwan Yoon; Jeong Min Lee (Journal of Liver Cancer)
Backgrounds/Aims Radiofrequency ablation (RFA) is widely employed for managing recurrent hepatocellular carcinoma (HCC) following transarterial chemoembolization (TACE). However, local tumor progression (LTP) after treatment remains a significant challenge. This study evaluates the efficacy of saline-perfused bipolar RFA using twin internally cooled-perfusion (TICP) electrodes in managing recurrent HCC post-TACE. Methods Between September 2017 and January 2019, 100 patients with 105 nodules (mean diameter, 1.6±0.5 cm) were prospectively enrolled. Bipolar RFA with TICP electrodes was performed under ultrasound-computed tomography/magnetic resonance fusion guidance. The primary outcome was the 2-year cumulative incidence of LTP. Results The technical success and technique efficacy rates were 100% and 97%, respectively. During a median follow-up period of 34.0 months (range, 3-41), the estimated LTP rates were 13.3% at 1 year and 17.7% at 2 years. Progression-free survival rates were 37.8% and 27.7% at 1 year and 2 years, respectively. Conclusions Saline-perfused bipolar RFA using TICP electrodes demonstrates promising results for recurrent HCC after TACE, achieving high technical success and effective local tumor control rates.